2014
DOI: 10.1136/bcr-2014-203950
|View full text |Cite|
|
Sign up to set email alerts
|

Lipoid proteinosis: pathognomonic clinical and radiological features

Abstract: A 22-year-old woman presented with a facial rash and hoarseness of voice. On examination, coarse waxy thickening and scarring was noted on the forehead and both the cheeks. The eyelid margins revealed a row of beaded papules termed 'moniliform blepharosis'. CT scan of the brain revealed bilateral, symmetric calcification of the amygdala of the hippocampal nuclei. This led to the diagnosis of lipoid proteinosis which is a rare genetic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…24 Genetics LP is a rare and autosomal recessive inherited disease. 5 27 According to the The Human Gene Mutation Database (HGMD) 71 pathogenic mutations in ECM1 have been reported in LP patients from different geographical areas, including 32 missense/nonsense substitutions, 9 splicing substitutions, 26 small deletions/insertions (indels) and 4 gross deletions/insertions. 28 Hamada et al, suggested a genotype-phenotype correlation based on the location of the mutation, with a slightly milder phenotype for patients with mutations in exon 7 compared to patients with mutations outside exon 7.…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…24 Genetics LP is a rare and autosomal recessive inherited disease. 5 27 According to the The Human Gene Mutation Database (HGMD) 71 pathogenic mutations in ECM1 have been reported in LP patients from different geographical areas, including 32 missense/nonsense substitutions, 9 splicing substitutions, 26 small deletions/insertions (indels) and 4 gross deletions/insertions. 28 Hamada et al, suggested a genotype-phenotype correlation based on the location of the mutation, with a slightly milder phenotype for patients with mutations in exon 7 compared to patients with mutations outside exon 7.…”
Section: Pathophysiologymentioning
confidence: 99%
“…11 Cutaneous manifestations usually arise during the first two years of life. 5 Neurpshychiatric symptoms of LP are more common in patients older than 10 years of age. 15 An et al…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations